The 'Chalk' and the 'Cheese': David Underdown, Regional Cultures and Popular Allegiance in the English Revolution. Issue 5 (30th May 2013) - Hughes, Ann; Smuts, Malcolm
Abstract This article identifies the most important themes in David Underdown's analysis of popular political allegiance in the English civil war, looking particularly at his understanding of regional contrasts and cultural conflict. It focuses on Revel, Riot and Rebellion, and discusses the debate on this major work as well as the ways in which its insights have been modified by more recent scholarship.